Impact of perioperative interruption of antithrombotic therapy on thrombotic and bleeding events in non-cardiac surgery. (4th February 2022) - Saito, K; Saito, Y; Muramatsu, T; Kitahara, H; Fujimoto, Y; Isono, S; Kobayashi, Y
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Antithrombotic therapy including antiplatelet agents and anticoagulants are prescribed for secondary prevention in patients with established cardiovascular disease. Although antithrombotic therapy is often interrupted before non-cardiac surgery with or without perioperative bridging anticoagulation, the impact on thrombotic and bleeding events remains uncertain.  Purpose: The aim of this study was to clarify the impact of perioperative interruption of anticoagulants on thrombotic and bleeding events in patients with established CVD undergoing elective non-cardiac surgery.  Methods: A total of 330 patients chronically treated with antithrombotic therapy for secondary prevention underwent elective non-cardiac surgery under general anesthesia, with the complete interruption of antithrombotic agents. The study endpoints included all-cause death, thrombotic events, and major bleeding complications after surgical procedures.  Results: Of 330 patients, 171 (51.8%) and 159 (48.2%) received antiplatelet agents and anticoagulants perioperatively. Atrial fibrillation (31.8%) and coronary artery disease (20.3%) were the major indications for antithrombotic regimens. Antithrombotic therapy was interrupted from 5 [2, 7] days before the surgery to 4 [2, 7] days postoperatively. Perioperative bridging therapy with unfractionated heparin was employed in 99 (30.0%) patients. During the hospitalization, 3 (0.9%) patients died due to non-cardiovascular causes. Thrombotic events and major bleeding occurred in 2 (0.6%) and 9 (2.7%) patients. Bridging therapy with heparin was non-significantly associated with an increased risk of bleeding events (5.1% vs. 1.7%, p = 0.09). In univariable and multivariable analyses, pre-operative hemoglobin level and operative duration were significantly associated with bleeding complications. Conclusions: In the present study, complete interruption of antithrombotic therapy resulted in a few thrombotic events with a numerically higher rate of bleeding events in patients undergoing elective non-cardiac surgery. Pre-operative hemoglobin level and operative duration were significantly associated with post-operative bleeding complications.